Draft genome sequences of four potential new species of the genus Bradyrhizobium isolated from root nodules of native legumes in Costa Rican forests - Fernández Vargas, Rachelle (2025)
Here, we report the draft genome sequences of four Bradyrhizobium spp. isolates obtained from root nodules of the native legumes Pentaclethra macroloba, Chamaecrista nictitans, Erythrina fusca and Zygia engelsingii in tropical forests of Costa Rica. Genomes ranged from 8.6 to 9.8 Mb with GC contents between 62.8% and 63.8%. Phylogenomic analysis, along with average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) comparisons, confirmed that these isolates represent potential new species. ANI values ranged from 88.3% to 90.3%, and dDDH values from 28.8% to 41.8%, compared with their closest Bradyrhizobium species. Functional annotation revealed some genes related to nitrogen fixation (nifA, nifB, nifH) and nodulation capacity (nodB, nodC, nodJ). These results provide insights into the diversity and symbiotic capabilities of Bradyrhizobium in tropical ecosystems.